Degradation of Hydrogen Sulfide in Stillage as Ethanol Industrial Waste by Acidithiobacillus thiooxidans and Pseudomonas putida with Aerobic Biofiltration Method in Bioreactor - Vivi Alvionita Sari; Sri Rachmania Juliastuti (Jurnal Teknik ITS, 2019)
Stillage or vinasse is a by-product or waste from the fermentation-distillation process of the bioethanol industry. Stillage is the bottom product of the ideal distillation column. Stillage has a high sulfur content. In this waste, the sulfur content was 1680 mg/L. This liquid wastes are dangerous if it discharges directly into the environment without pretreatment.  For this reason, pretreatment is needed to reduce the sulfur concentration of liquid waste (stillage) using biofiltration method. The objective of this research is to eliminate the content of H2S or sulfur in the wastewater of the bioethanol industry (stillage) by using aerobic bacteria such as Acidithiobacillus thiooxidans dan Pseudomonas putida. The method of this experimental work used biofiltration which are attached on wood chips by aerobic bacterial to form biofilms in the reactor. The process in this study was conducted in two steps. The first step was carried out by sulfur oxidizing bacteria such as A.thiooxidans and P. putida with a concentration of 10% and 20% (v/v) that growth on packing to form biofilms in the reactor for 13 days. Furthermore, as the second step the bacteria degraded H2S content of liquid waste with attached bacteria on packing for 15 days in biofiltration reactor. From the preliminary results of this study, reactor with 10% (v/v) A. thiooxidans on wood chips packing and 30% (v/v) concentration stillage can degraded H2S from 4.90 mg/L to 2.61 mg/L (46.73% removal efficiency) and for reactor with 20% (v/v) A. thiooxidans can degraded H2S from 4.90 mg/L to 2.43 mg/L (50.41% removal efficiency). Meanwhile, reactor with 10% (v/v) P. putida can degraded H2S from 4.90 mg/L to 2.90 mg/L (40.82% removal efficiency) and for reactor with 20% (v/v) P. putida can degraded H2S from 4.90 mg/L to 2.84 mg/L (42.04% removal efficiency).